2015
DOI: 10.12932/ap0547.33.3.2015
|View full text |Cite
|
Sign up to set email alerts
|

Amaranthus species around Bangkok, Thailand and the release of allergenic proteins from their pollens

Abstract: Water could damage pollens and time after shedding and significantly affected the amount of allergenic proteins released from pollen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Despite the widespread belief that rain clears the air of pollen, it has been shown that, when pollen comes into contact with water, its allergens can be liberated from the grain in just a matter of seconds [17][18][19]. The effect of extreme weather events such as heavy rains and thunderstorms could cause the release of very small particles from pollen grains, which are known as paucimicronic particles.…”
Section: Pollen Allergymentioning
confidence: 99%
“…Despite the widespread belief that rain clears the air of pollen, it has been shown that, when pollen comes into contact with water, its allergens can be liberated from the grain in just a matter of seconds [17][18][19]. The effect of extreme weather events such as heavy rains and thunderstorms could cause the release of very small particles from pollen grains, which are known as paucimicronic particles.…”
Section: Pollen Allergymentioning
confidence: 99%